2 Electrochemical Synthesis of Hypervalent Iodine Compounds - Bystron,Tomas; Jirasko,Martin (Hypervalent Halogens in Organic Synthesis, 2026)
Hypervalent iodine compounds (or iodanes) represent an interesting class of chemicals possessing a multivalent iodine atom. They are popular oxidation and ligand-transfer agents that are renowned for their versatility and selectivity, but also for their high cost and in some cases low stability. Compared to classical synthetic procedures, the electrochemical synthesis of these compounds offers significant benefits, such as increased safety, and potentially reduced cost and environmental impact. This review summarizes advances in the electrochemical synthesis of various iodanes, and briefly mentions their applications for in-cell and ex-cell mediation.
Keywords: Referencework; Science of Synthesis; hypervalent iodine compounds; electroorganic chemistry; iodanes; iodoarene oxidation; iodonium salts; iodanyl radicals; benziodoxolone; iodobenzenes; electrochemical synthesis; electrolysis; electrosynthesis; anodic oxidation; mediation; flow reactors